2015
DOI: 10.1517/13543784.2015.1048333
|View full text |Cite
|
Sign up to set email alerts
|

A synopsis of drugs currently in preclinical and early clinical development for the treatment of benign prostatic hyperplasia

Abstract: Existing preclinical and clinical trials have highlighted many promising therapies to treat BPH. Further investigation with larger clinical trials is needed to establish these drugs as standard therapies. As the number of drugs in the arsenal against BPH continues to grow, providers and patients will have to engage in a discussion that weighs the risks and benefits of each therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…BPH is a common prostate disease affecting older men. It is a major cause of lower urinary tract symptoms deteriorating the quality of life [24]. The BPH pathogenesis has been associated with factors such as genetic predisposition, hormonal imbalance, imbalance in cell proliferation and death and inflammation [25].…”
Section: Discussionmentioning
confidence: 99%
“…BPH is a common prostate disease affecting older men. It is a major cause of lower urinary tract symptoms deteriorating the quality of life [24]. The BPH pathogenesis has been associated with factors such as genetic predisposition, hormonal imbalance, imbalance in cell proliferation and death and inflammation [25].…”
Section: Discussionmentioning
confidence: 99%
“…2122 For LUTS associated with benign prostatic hyperplasia (BPH), randomized clinical trials (RCT) have demonstrated the efficacy of commonly used pharmacologic therapies in men, but the beneficial effects of treatment may not be generalizable, can be costly because of long-term use, and produce numerous, often intolerable side-effects, which reduces adherence. 23 For interstitial cystitis/bladder pain syndrome (IC/BPS) and chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), numerous medical interventions have been proposed; however, effective treatment remains elusive. Because IC/BPS and CP/CPPS commonly occur with non-urologic chronic pain conditions (e.g., fibromyalgia, irritable bowel syndrome, chronic fatigue syndrome) 24 that likely complicate treatment approaches, a comprehensive approach to assess and treat patients with these syndromes may lead to better clinical management and possibly to development of more effective therapies.…”
Section: Challenges With Current Treatment Of Lutsmentioning
confidence: 99%
“…At present, frequently used therapeutic drugs, including alphablockers and 5-a reductase inhibitors, are not completely effective in certain patients (Ventura et al 2011;Bechis et al 2014). Besides, anti-inflammatory drugs are not included in the list of clinical drugs for BPH treatment (Gupta et al 2015). Furthermore, non-steroidal anti-inflammatory drugs commonly used in clinics have side effects; thus, these drugs are not suitable for long-term use in patients with BPH (Geusens et al 2013).…”
Section: Introductionmentioning
confidence: 99%